You're a bad man, Mr Gum - Stanton, Andy (Modern Classics, 2016)
'It's time for action, ' said Mr Gum to nobody in particular. 'Nasty action.' Good evening. Mr Gum is a complete horror who hates children, animals, fun and corn on the cob. This book's all about him. And an angry fairy who lives in his bathtub. And Jake the dog, and a little girl called Polly. And there's heroes and sweets and adventures and Everything. You're a Bad Man, Mr Gum! is the first book in the internationally best-selling series by Andy Stanton, which has won everything from the Blue Peter Book Award (twice) to the Roald Dahl Funny Prize and the Red House Children's Book Award. This edition celebrates the 10th anniversary of its first publication. Worryingly splendid. (Guardian).